Administrative leadership: Understanding the preferred leadership roles of the Ethiopian civil service managers. Issue 3 (4th September 2017) - Mitiku, Adare Assefa; Hondeghem, Annie; Troupin, Steve
Abstract : Purpose: The purpose of this paper is to examine the leadership roles the Ethiopian civil service managers preferably embody in their setting. As such, contextually preferred roles were identified and briefly contrasted with the leadership literature. It also outlined the directions for the future research agenda. Design/methodology/approach: Q-methodology, an approach reasonably like "grounded-theory" was used. It is suited to embrace life as lived by the actors themselves. In this specific case, Q-methodology allows the managers to conceptualize their definitions or preferences of leadership roles. The data were obtained from 51 managers working in the federal civil service organizations covering a broad range of public policy and service fields. Findings: Based on the Q-sorts of 51 managers, the authors found three distinct yet interrelated archetypes of role preferences, which the authors labeled as the change agents, affective leaders and result-oriented realists. The study, however, demonstrates that although the ostensible echoes of each of these perspectives were professed, there were overlooked functions that are needed to be performed for full practice of each. Practical implications: Understanding the contextually preferred leadership roles, if considered in designing the management training and development programs, could prove productive. It also informs the staff recruitment and promotion activities of the civil service organizations. Originality/value: Conceptualizations of public leadership roles are abound in the literature. As they mostly emerged in a Western context, their applicability to other settings is questionable. Studying the subject in the context of Ethiopia, this paper contributes to the growing body of African literature on administrative leadership and informs the practice as well as the scholarship in this area.